Metal Mining’s Environmental Pressures: A Review and Updated Estimates on CO2 Emissions, Water Use, and Land Requirements - Tost, Michael; Bayer, Benjamin; Hitch, Michael; Lutter, Stephan; Moser, Peter; Feiel, Susanne (Sustainability, 2018)
The significant increase in metal mining and the inevitability of the continuation of this trend suggests that environmental pressures, as well as related impacts, have become an issue of global relevance. Yet the scale of the impact remains, to a large extent, unknown. This paper examines the mining sector’s demands on CO2 emissions, water use, as well as demands on land use focusing on four principal metals: iron, aluminium (i.e., bauxite ore), copper, and gold. These materials represent a large proportion of all metallic materials mined in terms of crude tonnage and economic value. This paper examines how the main providers of mining data, the United Nations, government sources of some main metal producing and consuming countries, the scientific literature, and company reports report environmental pressures in these three areas. The authors conclude that, in the global context, the pressure brought about by metal mining is relatively low. The data on this subject are still very limited and there are significant gaps in consistency on criteria such as boundary descriptions, input parameter definitions, and allocation method descriptions as well as a lack of commodity and/or site specific reporting of environmental data at a company level.